2015
DOI: 10.3201/eid2108.141878
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Distribution and Expansion of Human Lyme Disease, United States

Abstract: Lyme disease occurs in specific geographic regions of the United States. We present a method for defining high-risk counties based on observed versus expected number of reported human Lyme disease cases. Applying this method to successive periods shows substantial geographic expansion of counties at high risk for Lyme disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
163
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 209 publications
(168 citation statements)
references
References 14 publications
5
163
0
Order By: Relevance
“…Because of human population density and proximity to the heavily populated areas of the northeastern U.S., there is a continuing misconception that Lyme disease cases are on the rise only in northeast Pennsylvania [12]. But over the past decade, many counties in western Pennsylvania have experienced an increase in incidence of Lyme Borreliosis in human adults and children [11] which is corroborated by the latest CDC finding that "The center of the high-incidence focus in the northeastern United States generally moved westward and northward, away from the coast of northern New Jersey and into east-central Pennsylvania" [13].…”
supporting
confidence: 56%
See 2 more Smart Citations
“…Because of human population density and proximity to the heavily populated areas of the northeastern U.S., there is a continuing misconception that Lyme disease cases are on the rise only in northeast Pennsylvania [12]. But over the past decade, many counties in western Pennsylvania have experienced an increase in incidence of Lyme Borreliosis in human adults and children [11] which is corroborated by the latest CDC finding that "The center of the high-incidence focus in the northeastern United States generally moved westward and northward, away from the coast of northern New Jersey and into east-central Pennsylvania" [13].…”
supporting
confidence: 56%
“…Although the biotic and abiotic factors influencing the distribution of I. scapularis ticks and their transmission of the zoonotic pathogens they carry are complex [23] and beyond the scope of this manuscript, it is obvious that Lyme disease in southwest Pennsylvania is on the rise [11,13]. During a five year period (2010-2014), Pennsylvania Department of Health [11] reported a seven fold increase in Lyme disease incidence rate in southwest Pennsylvania (75.72 in 2014 versus 11.5/100,000 persons in 2010) as compared to a two-fold increase in northeast Pennsylvania (54.4 in 2014 versus 30.51 in 2010), which the CDC It has been previously reported that human Lyme and Babesiosis are commonly diagnosed in overlapping geographic areas, especially in regions with high human densities of the northeast (New York, New Jersey) and Midwest (Minnesota, Wisconsin) United States [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Globally, Lyme disease has been reported in more than 80 countries, and it appears to be on the rise. 3,7 The disease is complex, varying in its clinical presentation, and can at times be challenging to be reliably diagnosed using standard diagnostic tests, as discussed elsewhere in this issue. The life cycle of the pathogen and the ecological interactions that influence the risks of transmission to humans are also extremely complex, but are nonetheless important to understand in guiding the diagnosis, treatment, and control of the disease.…”
mentioning
confidence: 99%
“…Similarly whilst incidence across Western Europe is estimated at 56.03 per 100,000 people, it differs significantly between countries, ranging from 0.001 per 100,000 (Italy) to 464 per 100,000 (Sweden) [6]. In Europe, as in the USA [7,8], the geographic spread and reported number of clinical cases is rising in many areas [9][10][11]. In some countries the increase in reported cases may partly be explained by growing awareness amongst clinicians and the public about disease symptoms and transmission routes [12].…”
Section: Introductionmentioning
confidence: 99%